Foot of the Continental Slope of Sri Lanka - Tantrigoda, Dhammika A.; Fernando, M.M.P.M. (My University, 2005)
Foot of the continental slope of Sri Lanka has been determined using satellite bathymetry information downloaded from NOAA database (http://topex.ucsd.edu) employing the second derivative method. Foot of the continental slope of Sri Lanka is situated at an average distance of about 47 km. Its maximum and minimum distances from the zero height contour are 127 km. and 16 km. Almost 70% of the foot of continental slope occurs in the depth range of 2600 -3800 m.
Keywords: Continental margin; Continental slope